Great American speeches - Douglas, Melvyn 1901-1981; Price, Vincent 1911-1993; Begley, Ed 1901-1970; Sandburg, Carl 1878-1967 (Caedmon, 1958)
Presents speeches by Patrick Henry, George Washington, Thomas Jefferson, Josiah Quincy, Henry Clay, Charles Sumner, Robert Toombs, Abraham Lincoln, Robert E. Lee, and William Jennings Bryan
Program notes with texts of speeches bound in container
Liberty or death / Patrick Henry -- First inaugural address / George Washington -- First inaugural address / Thomas Jefferson -- On the admission of Louisiana / Josiah Quincy -- On the war of 1812 / Henry Clay -- The "house divided" speech / Abraham Lincoln -- The crime against Kansas / Charles Sumner -- The cooper union speech / Abraham Lincoln -- On secession / Robert Toombs -- The Gettysburg address / Abraham Lincoln -- Farewell to his troops (General order no. 9) / Robert E. Lee -- The "cross of gold" speech / William Jennings Bryan
Keywords: Geschichte; Speeches, addresses, etc., American; Rede; Präsident; United States / History; United States; USA; Schallplatte